Chapter Regional variation in the distribution of property rights over land in sixteenth-century Ottoman rural Manisa - Ceylan, Pınar (Datini Studies in Economic History, 2020)
Concentrating on the Western Anatolian district of Manisa and employing tax surveys dating 1575, this study points to the regional variation in property rights institutions, which resulted in different inequality regimes across space. Empirical evidence suggests the existence of two agricultural production systems characterized by different property and surplus relations, in the southern and northern parts of the district in the late sixteenth century. Accordingly, inequality structures in these areas reflected region-specific patterns of property rights distribution within and across direct producers and landlords' classes.